Effect of Educational Program on Prophylactic Antiemetics Prescribing Practice - Zaid M.A Yousif; Ayad Ali Hussein (College of Pharmacy / Mustansiriyah University, 2019)
Background: Post-operative nausea and vomiting (PONV) continues to be among the main concerns after general anesthesia, impacting approximately 30% of all postoperative patients. PONV is still reported by patients as their most distressing post-surgical outcome even    surpassing that of pain. In spite of the presence of PONV prophylaxis guidelines and the availability of multimodal and novel anti-emetics, it is clear that these guidelines are poorly applied with insufficient prescription of pre-emptive anti-emetics. This study aimed at evaluating the effect of educational intervention with general surgeons and anesthesiologists on prophylactic antiemetic prescribing practice. Methods: An interventional study was carried out at Al-Sader Medical City/ Al-Najaf province/ Iraq. In the observational phase of the study, patients were selected from the general surgery ward to observe the baseline prescribing pattern of the prophylactic anti-emetics and PONV incidence among them. After implementing the educational program, another group (interventional group) of patients was taken to see if there was any alteration in the practice of pre-emptive anti-emetics prescription and the incidence of PONV. Results: Two groups each of 50 patients were enrolled, namely, observational group and interventional group. In the observational group, only 7 patients (14%) received preoperative prophylactic anti-emetics compared to 24 patients (48%) in the interventional group, (P<0.001). No statistically relevant difference was observed in the use of post-operative anti-emetics. The incidence of PONV within the first 24 hours was significantly lower among the interventional patients' group, (28%) versus (54%) before the educational intervention, (P<0.05). Conclusion: This study revealed that the educational program done by the researcher has a positive impact on the prescription of pre-operative prophylactic anti-emetics with subsequent reduction in PONV incidence.